2018
DOI: 10.1016/j.epsl.2018.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Reactive transport under stress: Permeability evolution in deformable porous media

Abstract: We study reactive transport in a stressed porous media, where dissolution of the solid matrix causes two simultaneous, competing effects: pore enlargement due to chemical deformation, and pore compaction due to mechanical weakening. We use a novel, mechanistic pore-scale model to simulate flooding of a sample under fixed confining stress. Our simulations show that increasing the stress inhibits the permeability enhancement, increasing the injected volume required to reach a certain permeability, in agreement w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Here γ=c0/csolθ is the acid capacity number, defined as the ratio between the number of molecules in a unit volume of mineral to the number of molecules of reactant in a unit volume of the incoming fluid, with θ accounting for the reaction stoichiometry. To account for a finite amount of soluble solid, once locally solid is fully dissolved between adjacent pores, these pores are merged (see Roded et al., 2018).…”
Section: The Pore Network Modelmentioning
confidence: 99%
“…Here γ=c0/csolθ is the acid capacity number, defined as the ratio between the number of molecules in a unit volume of mineral to the number of molecules of reactant in a unit volume of the incoming fluid, with θ accounting for the reaction stoichiometry. To account for a finite amount of soluble solid, once locally solid is fully dissolved between adjacent pores, these pores are merged (see Roded et al., 2018).…”
Section: The Pore Network Modelmentioning
confidence: 99%
“…Then, the total volume of mineral dissolved from a single channel surface during a time step Δ t can be calculated using normalΔVdiss=2italicπrnormalΔtλeffνcsol0l()ceqc()xnormaldx=normalΔitalict.2emqceqcinνcsol()1esλeff/q.In order to keep the model tractable, we assume that each cylindrical channel dissolves uniformly along its length. The corresponding change in channel radius is then normalΔr=normalΔVdisss=normalΔitalictqs()ceqcinνcsol()1esλeff/q.The model also accounts for a finite amount of soluble solid, and if locally between adjacent channels solid is fully dissolved, channel merging is accounted for by the associated hydraulic conductivity increase (see Roded et al, 2018).…”
Section: The Network Modelmentioning
confidence: 99%
“…The model also accounts for a finite amount of soluble solid, and if locally between adjacent channels solid is fully dissolved, channel merging is accounted for by the associated hydraulic conductivity increase (see Roded et al, 2018).…”
Section: Reactive Transport and Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D reactive transport simulations conducted by Wolf et al have found a distinct inner region of 2000 m radial distance under the dominating impact of dissolved CO 2 [23]. Near the injection well, increasing the stress which impact mainly depends on the dissolution regime inhibited the permeability enhancement, increasing the injected volume required to reach a certain permeability [24]. Wang et al have predicted a maximum 3.2% permeability increase of the reservoir and a maximum 1.1% permeability increase of the caprock after 1000 years of exposure to CO 2 -rich brine under the convection mechanism [25].…”
Section: Introductionmentioning
confidence: 98%